2005
DOI: 10.1158/0008-5472.can-04-3132
|View full text |Cite
|
Sign up to set email alerts
|

Dominant-Negative Notch3 Receptor Inhibits Mitogen-Activated Protein Kinase Pathway and the Growth of Human Lung Cancers

Abstract: Notch3 is a member of an evolutionarily conserved family of cell surface receptors important in cell-fate determination in both vertebrates and invertebrates. Significant data support the role of Notch pathway in cancer development, although the conflicting role of Notch signaling pathways in tumorigenesis suggests that its action is highly context-dependent. Furthermore, although Notch receptors signal primarily through the regulation of hairy enhancer of split (HES) and HES-related (HRT) genes, they are know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
140
3
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(161 citation statements)
references
References 50 publications
15
140
3
3
Order By: Relevance
“…Notch3 was reported to be overexpressed in about 40% of NSCLC, and its chromosomal translocation has been detected in certain lung cancer tissue, suggesting that Notch3 could be an oncogene in NSCLC (Haruki et al, 2005). Previous studies also documented that Notch1 was frequently expressed in lung cancer and correlated with the malignancy of NSCLC (Collins et al, 2004).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Notch3 was reported to be overexpressed in about 40% of NSCLC, and its chromosomal translocation has been detected in certain lung cancer tissue, suggesting that Notch3 could be an oncogene in NSCLC (Haruki et al, 2005). Previous studies also documented that Notch1 was frequently expressed in lung cancer and correlated with the malignancy of NSCLC (Collins et al, 2004).…”
Section: Resultsmentioning
confidence: 97%
“…Aberrant expression of Notch in NSCLC has been illustrated in various studies (Collins et al, 2004;Haruki et al, 2005;Kunnimalaiyaan and Chen, 2007). Notch3 was reported to be overexpressed in about 40% of NSCLC, and its chromosomal translocation has been detected in certain lung cancer tissue, suggesting that Notch3 could be an oncogene in NSCLC (Haruki et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The therapeutic efficacy of notch inhibitors has been observed in other human cancer cell lines (Haruki et al, 2005;Park et al, 2006). Although pharmacological therapy with GSI-I was very effective in vitro, it was less effective in vivo, probably because of diffusion-limited effects of either tissue solubility or half-life.…”
Section: Notch 3 Dependency Of Ibc Embolus Y Xiao Et Almentioning
confidence: 99%
“…Recent studies have shown that Notch3 signalling in VSMC plays an important role in down-regulating Fas-Ligand (FasL)-induced apoptosis (extrinsic apoptotic pathway) (30). Involvement of Notch3 in the regulation of apoptosis has also been observed in other cell types, such as lung carcinoma cells, where inhibition of the Notch3 signalling pathway mitigates the neoplastic phenotype (31). Finally, Viswanathan et al (2006) found widespread neuronal apoptosis in the cerebral cortex of CADASIL brains, demonstrating that the degree of neuronal apoptosis is related to the underlying subcortical white matter damage (32).…”
Section: Cadasilmentioning
confidence: 99%